Cinema com o Brejo : experiências de criação com os espaços em processos de formação audiovisual no Maciço de Baturité/CE - Leonardo Mont'Alverne Câmara (2022)
This research focuses on the pedagogical process and the experiences of audiovisual creation lived in the core of the Cinema no Brejo project, carried out with young students from different rural locations in Maciço de Baturité, Ceará. From a heterogeneous set of materials produced during the training course – such as photographs, videos, drawings and films –, we intend to investigate the ways in which the experience of young people with cinema has been constituted as a way of sensitive relationship with their spaces. We will handle the report and cartography as an artifice to articulate, through writing, the formal dimensions of the images to the learning and creation experiences that mark them and from which they derive. In the company of the films Caridade, Modos de Vida, Lavadeiras and Serra dos ETs, made by the students in the final stage of the course, we will pay attention to certain traces left by the production processes in their visible dimensions to, from a cartographic gesture, perceive the relationships and experiences that point to certain forms of the processes. In contact with these forms, forged, discovered and practiced during the meetings, we will try to circumscribe a double role of cinema in this formative experience: on the one hand, entangled in the ways of life and the daily lives of young people. On the other hand, it is managed as an artifice of creation, enabling other ways of perceiving, learning and inventing with the world.